Indagações, Comentários e Saberes dos Educandos - Jovens e Adultos - - Vagner de Araújo Gabriel; Maria Rosa Martins Rodrigues de Camargo (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
This text comments on the importance of the usage of class recording in planning lectures as well as scientific material. It surveys and analyzes young and adults students speeches. These students were members of a class of youth and adults linked to the Project of Youth and Adult Education (PEJA), at the Universidade Estadual Paulista, at the Campus of Rio Claro. Speechs related to Biological Science subjects were detached from the records and analyzed considering their meaning and the moment they were pronounced. The text also presents a class report that was planned and developed based on those class recordings. The student's life experiences are very important to develop a lecture. It is recognized the importance of the dialogue between students and teachers, once the relationship between learning and teaching is a back and forth mechanism from teacher to student and the analyzes of class recordings are an important source of qualitative data.